2021
DOI: 10.2217/fon-2021-0218
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Characteristics and Outcomes of Advanced Non-Small-Cell Lung Cancer Patients with EGFR Exon 19 Deletions or Exon 21 Mutations

Abstract: Aim: To estimate real-world (rw) outcomes for first-line therapy in patients with advanced EGF receptor ( EGFR)-mutated non-small-cell lung cancer (NSCLC), focusing on specific mutation types. Patients & methods: Retrospective observational study (n = 244 patients). Results: Univariate/multivariate analyses showed longer rw progression-free survival (rwPFS) and rwPFS2 in patients with ex19del versus Leu858Arg mutations. Median overall survival was 12.3 months longer with ex19del versus Leu858Arg mutations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
2
4
0
Order By: Relevance
“…The survival analysis showed that the prognosis of targeted therapy was better than chemotherapy in patients with EGFR mutant type, which was consistent with previous studies ( 43 , 44 ). However, there is no significant difference in survival time between patients with E19 and E21, furthermore, the survival rate of patients with E19 was better than that with E21, which was similar to previous study ( 45 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The survival analysis showed that the prognosis of targeted therapy was better than chemotherapy in patients with EGFR mutant type, which was consistent with previous studies ( 43 , 44 ). However, there is no significant difference in survival time between patients with E19 and E21, furthermore, the survival rate of patients with E19 was better than that with E21, which was similar to previous study ( 45 ).…”
Section: Discussionsupporting
confidence: 90%
“…Exon 19 deletion (E19) and exon 21 L858R missense (E21) are the two most common EGFR-TKIs-sensitive EGFR mutation subtypes. There is a difference in treatment strategy, response and prognosis between patients with EGFR E19 and E21 ( 4 , 5 ). Therefore, identifying EGFR mutation status and subtypes are important for the treatment of patients with lung adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…As also previously reported [ 31 , 48 ], TP53 co-mutations were generally not associated with other measured prognostic factors (e.g., age, sex, smoking status, ECOG PS, baseline brain metastases), EGFR mutation subtype, or treatment assignment. Lastly, consistent with guideline recommendations [ 7 , 8 ] and prior studies [ 53 ], most patients with EGFR -mutated aNSCLC received EGFR -TKI monotherapy (predominantly osimertinib) in the 1 L and 2 L settings in current study, with few patients receiving 1 L EGFR -TKI combinations with either anti-angiogenics or chemotherapy.…”
Section: Discussionsupporting
confidence: 78%
“…In line with previous studies linking a TP53 co-mutation with reduced sensitivity to EGFR -TKIs [ 29 , 49 ], a TP53 co-mutation was associated with worse outcomes in the current dataset, even after adjustment for known aNSCLC prognostic factors including age, sex, smoking history, performance status, and baseline brain or bone metastases. Our findings also suggest that TP53 co-mutations in the context of the EGFR mutation subtype may impact response to treatment and the survival outcomes, as the negative survival effect associated with TP53 co-mutations has been observed to occur less among patients with EGFR exon 19 deletions than exon 21L858R mutations [ 31 , 32 ] and is likely because EGFR exon 19 deletions are known to be more responsive to EGFR -TKIs [ 53 , 54 ], as also demonstrated by our results. Notably, this finding appears to be driven by the robust OS in patients with TP53 wild-type tumors plus the exon 19 deletion subgroup (47.1 months), as the OS was similar between the exon 19 deletion subgroup plus a TP53 co-mutation (25.6 months) and an exon 21L858R mutation plus the TP53 co-mutation subgroup (28.7 months).…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, the independent factors for PFS prolongation were exon 21 L858R and dose reduction within 6 months. Generally, exon 19 deletion is associated with greater antitumor efficacy of EGFR-TKIs than exon 21 L858R [ 19 ]. PD-L1 TPS ≥ 50% is a poor prognostic factor for osimertinib therapy [ 10 ].…”
Section: Discussionmentioning
confidence: 99%